2012
DOI: 10.1016/j.compedu.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laptop-free zones on student performance and attitudes in large lectures

Abstract: The goal of this study was to determine if laptop use in lecture negatively impacts learning outcomes of surrounding students taking notes on paper. Two sections of a large introductory biology course (>400 students/section) were zoned into a laptop-permitted and a laptop-free area. Two sections in which laptop users could sit anywhere served as the Control. There was no difference in the attendance (w85%) or percentage of students using laptops (w29%) between Zoned and Control sections. Academic performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 18 publications
1
60
0
Order By: Relevance
“…When technology is used independently, it often does not result in learning (Aguilar-Roca et al, 2012). Additionally, prior computer experience plays a role in a student's perception of online learning methods (Top, 2012).…”
Section: Interactions Between Group Members and Supervisorsmentioning
confidence: 99%
“…When technology is used independently, it often does not result in learning (Aguilar-Roca et al, 2012). Additionally, prior computer experience plays a role in a student's perception of online learning methods (Top, 2012).…”
Section: Interactions Between Group Members and Supervisorsmentioning
confidence: 99%
“…Aguilar-Roca, Williams, & O'Dowd [19] found that information seeking process (when taken up collaboratively by group) yields more fruitful results as compared to information seeking activity done individually. This not only points to another emerging area of research i.e., Collaborative Information Seeking but also establishes that QA websites enhance collaboration among researchers.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For example, in a 2010 study of undergraduate business students (Kraushaar & Novak, 2010), users accessed an average of 65 tasks (windows) per lecture, of which 65% were classified as distractive (not related to the lecture material) and distractive tasks were active for 42% of the lecture time -which is in line with the estimates for off-topic task use in this study. However, estimates of off-task laptop and smartphone use during lectures do vary considerably, with recent results ranging from as high as 84% (Gehlen-Baum & Weinberger, 2012) to as low as 16% (Aguilar-Roca, Williams, & O'Dowd, 2012).…”
Section: Task Frequencies and Durationsmentioning
confidence: 99%